Investigation on the potential use of plastic fibre to improve consolidation behaviour in earthwork applications / Nor Hafizah Hanis Abdullah ... [et al.] - Abdullah, Nor Hafizah Hanis; Izani, Muhammad Syahiran Wazini; Keria, Roziah; Musir, Adhilla Ainun (2019)
Problems of excessive settlement due to consolidation process in compressible soil is inevitable at some construction sites in Malaysia. For earthworks, soil with good bearing capacity and strength is required to support the structural loads. Sometimes, locally available soil is not eligible for construction works. Soil improvement method is needed to make sure the stability and control of soil settlement of the embankment. In this paper, an experimental work has been carried out to investigate the potential of plastic fibre to improve soil consolidation behaviour. The soil-plastic fibre (as reinforcement material) is compacted at optimum moisture content with different percentage of the plastic fibre i.e. 0.25%, 0.5%, 1% and 2%. 1D-consolidation oedometer test was carried out for this purpose. After the laboratory study was conducted, the coefficient of volume change (mv) and compression index (Cc) increase from 0% up to 1% and only shows sign of reduction at 2% of the solid plastic fibre. As for the coefficient of consolidation (Cv), the value increase with the increment of the percentage of plastic fibre used. Meanwhile, the time rate of consolidation (t90) of the soil reduces as the percentage of the plastic fibre increases. Therefore, the plastic fibre as soil reinforcement to reduce settlement has the potential to be used given that the amount of plastic fibre is more than 2%.